1998
DOI: 10.1001/archinte.158.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Incidence of Deep Vein Thrombosis and Pulmonary Embolism

Abstract: Venous thromboembolism is a major national health problem, especially among the elderly. While the incidence of pulmonary embolism has decreased over time, the incidence of deep vein thrombosis remains unchanged for men and is increasing for older women. These findings emphasize the need for more accurate identification of patients at risk for venous thromboembolism, as well as a safe and effective prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

85
1,568
18
102

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 2,487 publications
(1,815 citation statements)
references
References 10 publications
85
1,568
18
102
Order By: Relevance
“…With nearly 10 million annual cases worldwide and an individual lifetime risk of >8%, VTE represents the third leading cause of vascular disease 1, 2, 3. VTE is associated with significant morbidity and mortality, accounting for >200 000 deaths in the United States annually 4.…”
Section: Introductionmentioning
confidence: 99%
“…With nearly 10 million annual cases worldwide and an individual lifetime risk of >8%, VTE represents the third leading cause of vascular disease 1, 2, 3. VTE is associated with significant morbidity and mortality, accounting for >200 000 deaths in the United States annually 4.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, venous thromboembolism (VTE) is estimated to occur in about 100 persons per 100 000 annually, with about two thirds of cases being DVT 1, 2, 3. The economic and healthcare system burden of VTE is substantial, with estimated annual costs ranging from $13.5 to $27.2 billion (2011 US dollars) 4…”
Section: Introductionmentioning
confidence: 99%
“…Since the first description of an association between VTE and cancer by Trousseau (1868), cancer has emerged as an important risk factor for VTE. A prospective medical database of a county population in the United States reported cancer alone as associated with a 4.1-fold increase in risk of VTE, compared to the annual incidence of a first episode of VTE in the general population of 117 out of 100 000-capita (Silverstein et al, 1998;Heit et al, 2000). Conversely, Sørensen et al (2000) reported that 1-year survival rate was significantly lower in cancer patients with VTE (12%) than in cancer patients without VTE (36%), and the mortality ratio associated with VTE was 2.2 for the 1-year follow-up period.…”
mentioning
confidence: 99%